The effect of e-retailers' innovations on shoppers' impulsiveness and addiction in web-based communities: the case of Amazon's Prime Now. (10th October 2019) - Ramadan, Zahy B.; Farah, Maya F.; Daouk, Shireen
In the era of exponential growth of online shopping, e-commerce has accelerated consumers' shift from offline to online shopping, specifically in the FMCG industry. In 2015, Amazon launched the Amazon Prime Now service based on same-day delivery. The research objective is to understand the implications of this ordering tool on the consumer journey from the shopper web-based community, the retailer and brand perspectives. In order to investigate the usage of Amazon Prime Now and its impact on the overall consumer journey, a survey was devised and completed by 25 Prime users who reside in the UK. The findings show that clients' gratification is due to the outstanding customer service Amazon offers, which as a result established a trust and love relationship with the retailer. Moreover, the findings show that while the minimum order fees have reduced shoppers' impulsive behaviour in web-based communities, an overall addiction toward the use of Amazon Prime Now was taking place.